Techniques and Management Policies Used by Romanian Banks in Transylvania:A Case Study of “Someşana” Bank (Solnoc-Dăbâca County) - Radu, Gavrilă Pavel (Asian Journal of Empirical Research, 2012)
To thrive, the Romanian peasant needed primarily to obtain credit, especially credit on favorable terms. Romanians from Transylvanian adopted a prudent policy, but one that defended their economic interests.Romanian credit institutions from Transylvanian were formed and evolved in a complex financial framework. In economy of Solnoc-Dăbâca County banks were growth poles.The most representative Romanian Bank, which polarizes a lot of requests for loans from Romanian peasants, was "Someşana". Executive Director, Dr. TeodorMihali, was a lawyer and one of the most influential members of the Romanian National Party. He was a leader of the Romanian community in Solnoc-Dăbâca County, and in Transylvania.The main policy practiced by all Romanian banks was the pursuit of profit growth and mainly the payments of dividends. The bulk of the profits made by Romanian banks are primarily divided amongst the shareholders in the form of dividends and supra-dividends. Applying the technique for banking safety, a significant percentage of the net profit was allocated to the reserve fund and the additional reserve fund. The amounts allocated for charity by the Romanian banks, amounts annually to several tens of thousands of koroane.As an important part of internal organization can be considered the use of employees, called "men of confidence", which played a significant role in very good relationship between customers and the bank. The Management for the "Someşana" Bank, as in fact most of the Romanians leaders in Transylvania, acted with intelligence to achieve a balance between the payout to shareholders, officers and community (church, school, etc.).But the greatest achievement that actually ensured the viability and vitality of the bank was creating and maintaining a strong link with its customers: the Romanian peasants. The link was not only economic but national as well.